2021
DOI: 10.2147/jir.s304461
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138-5p Regulates Hippocampal Neuroinflammation and Cognitive Impairment by NLRP3/Caspase-1 Signaling Pathway in Rats

Abstract: Purpose Neuroinflammation is an essential causative factor in the pathogenesis and progression of cognitive impairment. The present study aims to evaluate the critical role of microRNA-138-5p (miR-138-5p) in hippocampal neuroinflammation and cognitive impairment through the NLRP3/caspase-1 signaling pathway in rats. Material and Methods We established the cognitive impairment rat model and RM (Rat microglia) microglial cellular inflammation model by intracerebroventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
(79 reference statements)
1
21
0
Order By: Relevance
“…Evidence has previously been presented suggesting that increased formation of miR-138-5p is beneficial for the cognitive function of LPS-treated rats, and the reason might be attributed to its suppression of neuroinflammation and neuron cell apoptosis [23]. Besides, Feng et al [24] also propose the close relationship between the downregulation of miR-138-5p and impaired learning and memory in LPS-treated rats, the underlying mechanism might be correlated with its beneficial effect against neuroinflammation. From another perspective, both neuroinflammation and neuronal apoptosis have been indicated to deteriorate neurological function [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Evidence has previously been presented suggesting that increased formation of miR-138-5p is beneficial for the cognitive function of LPS-treated rats, and the reason might be attributed to its suppression of neuroinflammation and neuron cell apoptosis [23]. Besides, Feng et al [24] also propose the close relationship between the downregulation of miR-138-5p and impaired learning and memory in LPS-treated rats, the underlying mechanism might be correlated with its beneficial effect against neuroinflammation. From another perspective, both neuroinflammation and neuronal apoptosis have been indicated to deteriorate neurological function [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…miR-138-5p has been found to be a metastatic and tumour suppressor in different types of diseases [ 25 29 ]. Our previous study found that miR-138-5p plays a vital role in neuroinflammation by targeting NLRP3 and this phenomenon can cause cognitive impairment [ 30 ]. The NLRP3 protein is a crucial element of the multifunctional inflammasome complex in the inflammatory signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-138-5p has been found to be a tumour suppressor in bladder [ 25 ], non-small cell lung [ 26 ], colorectal [ 27 ], malignant glioblastoma [ 28 ], and pancreatic cancer [ 29 ]. Our previous study found that miR-138-5p plays a vital role in cognitive impairment by targeting NLRP3 [ 30 ]. We also predicted that with RNA sequencing (RNA-seq) and bioinformatics analysis, the lncRNA NONRATT004344/miR-138-5p/NLRP3 ceRNA network (ceRNET) could regulate NLRP3-triggered inflammatory responses in ALI [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-138–5p can directly target the 3′-UTR of NLRP3 and inhibit the expression of NLRP3. Up-regulation of miR-138–5p inhibits the activation of NLRP3/caspase-1 axis and microglia, thereby attenuating hippocampal neuroinflammation and improving the cognitive function of the rat model ( Feng et al, 2021a ). MicroRNA-223 also directly targets and inhibits the expression of NLRP3, thereby reducing LPS-induced inflammation in microglia and improving neuronal function ( Zhang et al, 2020 ).…”
Section: Nlrp3 Inflammasome Inhibitors As a Potential Target For The ...mentioning
confidence: 99%